Preparation method and application of double-sided heterogeneous drug-loading wet hydrogel
By introducing Janus structures of THMA and PEGDA into the hydrogel material, the problem of insufficient adhesion of existing hydrogels in humid environments is solved, and the dual effect of tissue repair and prevention of postoperative adhesions is achieved, which is especially suitable for muscle starting and ending points repair.
Patent Information
- Application Number
- CN202411919893.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing hydrogel materials lack adhesion in wet environments, making it difficult to achieve the dual needs of tissue repair and prevention of postoperative adhesions at the same time, especially in the repair of muscle starting and ending points, lacking suitable wet adhesives.
Using Janus hydrogel based on THMA and PEGDA, a double-sided heterogeneous drug-loaded wet hydrogel was prepared through the hydrogen bonding characteristics of N-[tris(hydroxymethyl)methyl]-acrylamide (THMA) and the toughness provided by polyethylene glycol diacrylate (PEGDA), which has excellent drug release and anti-tissue adhesion effects.
While promoting soft tissue repair under basic mechanical strength, it prevents tissue adhesion through its unique non-adhesive surface, significantly enhances the effect of muscle and ligament surgery, and provides the dual function of drug release.
Smart Images

Figure CN119746132A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical and sanitary materials, and in particular to a preparation method and application of a double-sided heterogeneous drug-loaded wet hydrogel that is beneficial to drug release Background Art
[0002] Muscle insertion injury is a common chronic sports injury, usually caused by acute trauma or long-term overuse. The injury may involve complete or partial rupture of the tendon, seriously affecting the patient's daily life and exercise ability. The soft tissue adhesives currently available on the market cannot avoid tissue adhesion, which not only affects the healing effect of the rotator cuff, but may also cause postoperative pain and dysfunction in patients; on the other hand, local drugs cannot be effectively used.
[0003] Hydrogel materials are widely used in the fields of tissue engineering and regenerative medicine due to their excellent biocompatibility and adjustable mechanical properties. However, the existing hydrogel materials have insufficient adhesion in a wet environment, and it is difficult to simultaneously meet the dual needs of tissue repair and prevention of postoperative adhesion. Although there are already some applications of wet adhesives or Janus hydrogels, such as a Janus hydrogel with asymmetric and reversible adhesion properties developed by researchers from Southern Medical University to promote myocardial cell maturation and function; or a Janus porous PVA hydrogel suitable for soft tissue defect repair developed by researchers from Sun Yat-sen University, etc., there is still no suitable wet adhesive for repairing muscle enthesis injuries.
[0004] Therefore, it is a technical problem that technicians in this field urgently need to solve to provide a new type of heterogeneous double-sided hydrogel that can ensure that the hydrogel has basic mechanical strength, promotes the repair of soft tissue by using adhesion, and prevents tissue adhesion by using its unique non-adhesive surface. Summary of the invention
[0005] In view of this, the present invention provides a Janus hydrogel based on THMA and PEGDA that is conducive to drug release and a hydrogel material for preventing adhesion. The present invention utilizes the hydrogen-bond-rich properties of N-[tris(hydroxymethyl)methyl]-acrylamide (THMA) and combines the toughness provided by PEGDA to achieve an ideal effect.
[0006] A method for preparing a double-sided heterogeneous drug-loaded wet hydrogel, characterized in that it comprises the following steps:
[0007] (1) Preparation of functional particles loaded with anti-inflammatory drugs:
[0008] (11) mixing anhydrous ethanol, water and ammonia water, stirring and dissolving in an oil bath, and then adding tetraethyl orthosilicate and continuing to stir and react; after the reaction is completed, centrifuging and washing to obtain solid silica nanoparticles;
[0009] (12) dispersing the solid silica nanoparticles in water, stirring, and then centrifuging and washing again to obtain hollow mesoporous silica nanoparticles;
[0010] (13) dissolving baicalein in anhydrous ethanol, adding hollow mesoporous silica nanoparticles, stirring in a water bath, evaporating the ethanol and then freeze-drying to obtain hollow mesoporous silica-supported baicalein nanoparticles;
[0011] (2) Preparation of Janus hydrogels carrying functional particles (with adhesion effect):
[0012] (21) Dissolve N-trihydroxymethyl methacrylamide in water, add polyethylene glycol diacrylate, and mix them thoroughly; add hollow mesoporous silica-loaded baicalein nanoparticles; dissolve an appropriate amount of sodium alginate in the above solution, and after it is fully dissolved, obtain a mixed solution, and add the mixed solution into a silicone mold.
[0013] (22) adding phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt (initiator) into water to obtain an initiator solution; adding the initiator solution into a silica gel mold containing the composite solution, mixing evenly, and then irradiating with ultraviolet light of 365 to 405 nm for 5 to 10 minutes to obtain a solidified hydrogel;
[0014] (3) Preparation of the sliding side of the Janus hydrogel (the adhesion effect disappears on the immersed side): Place one side of the solidified hydrogel in the modified solution and soak for 30 to 45 seconds, then use water to remove excess solution on the surface of the hydrogel, wipe it with dry filter paper to form a sliding side, and obtain a double-sided heterogeneous drug-loaded wet hydrogel.
[0015] Further, the oil bath temperature in step (11) is 50°C;
[0016] The mass ratio of anhydrous ethanol, water and aqueous ammonia is (70-75):10:(3-4);
[0017] The amount of tetraethyl orthosilicate added is 3-6 ml / 100 ml of the mixed solution.
[0018] Furthermore, the stirring temperature in step (12) is 40-60°C and the stirring time is 24-36h.
[0019] Furthermore, in step (13), the water bath temperature is 50-60° C., and the water bath stirring time is 6-8 h;
[0020] The mass ratio of baicalein to hollow mesoporous silica nanoparticles is 1-2:3.
[0021] Furthermore, in step (21), the mass ratio of the N-trimethylol methacrylamide to the polyethylene glycol diacrylate is 1:0.02-0.06;
[0022] The amount of the hollow mesoporous silica-supported baicalein nanoparticles added is 1 mg / ml solution;
[0023] The amount of sodium alginate added is 0.3-0.7 wt % of the total mass of the solution.
[0024] Furthermore, the initiator in step (22) is LAP initiator or VA086 initiator.
[0025] The concentration of the initiator solution is 100ug / ml;
[0026] The added amount of the initiator is 2.5wt‰ of the mass of the mixed solution.
[0027] Further, the modified solution in step (3) is a borax solution or a CaCl 2 Solution.
[0028] Furthermore, in step (3), the concentration of the borax solution is 0.4 mM, and the CaCl 2 The concentration of the solution was 0.9% (m / v).
[0029] The beneficial effect of adopting the above further scheme is that borax, as a strong base and weak acid salt, can form a weak alkaline environment in water, promote the deprotonation of amino groups, accelerate the amidation reaction, and affect the surface viscosity. 2 (SO 4 ) 3 , CH3COONa and other strong bases and weak acid salts may have the same properties. On the other hand, they can be 2 et al. started from the perspective of influencing the properties of sodium alginate (SA), forming ionic bonds with the carboxyl groups therein, thereby causing cross-linking between the sodium alginate molecular chains, thereby changing the three-dimensional network structure of the hydrogel.
[0030] The present invention also provides application of the double-sided heterogeneous drug-loaded wet hydrogel prepared by the above method in medical materials.
[0031] The beneficial effects of the present invention are:
[0032] The present invention prepares hydrogels with excellent performance suitable for different mechanical strength scenarios. THMA enhances the stretchability and adhesion of the gel through a rich hydrogen bond network, while the high molecular weight PEGDA provides toughness and cross-linking degree. Sodium alginate further improves the viscosity of the gel, making it have strong adhesion on various surfaces. LAP and the like are used as photoinitiators to quickly initiate polymerization reactions under ultraviolet light irradiation, achieve rapid gelation, and are suitable for rapid preparation. By adjusting the ratio of PEGDA and SA, the strength and toughness of the gel can be optimized.
[0033] The present invention utilizes the characteristics of the hydrogel itself. The borate ions in the borax solution can chelate with the polar groups on the surface of the hydrogel and interact with each other, thereby changing the chemical composition and surface energy of the hydrogel surface, thereby adjusting its hydrophilicity and affecting its adhesion and sliding properties. Similarly, the metal ions in the calcium chloride and magnesium sulfate solutions form stable complexes with the hydroxyl groups in the hydrogel through chelation, while enhancing the mechanical properties, forming two sides with different structures, which is suitable for application scenarios to prevent postoperative tissue adhesion.
[0034] The hydrogel prepared by the present invention can be given multiple functions, such as antibacterial property, electrical conductivity or optical properties, by further chemical modification or physical treatment. This multifunctionality makes the hydrogel have potential in a wide range of application fields.
[0035] In summary, the hydrogel prepared by the present invention can not only regulate inflammation and reduce the occurrence of complications during postoperative recovery, but also has excellent anti-tissue adhesion effect, effectively solving many problems in the prior art and significantly improving the effect of muscle and ligament surgery. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the biocompatibility test results of the hydrogel provided by the present invention.
[0037] Figure 2 This is an influence diagram of the maximum tensile load on the tendon tissue of rats with rotator cuff injury provided by the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] A method for preparing a Janus hydrogel that is beneficial to drug release:
[0041] (1) Preparation of functional particles loaded with anti-inflammatory drugs
[0042] (11) 14 mL of anhydrous ethanol, 2 mL of deionized water, and 0.5 mL of aqueous ammonia were added to a round-bottom flask and stirred in an oil bath at 50 °C for 20 min to fully dissolve the mixture. After adding 0.5 mL of tetraethyl orthosilicate, the mixture was heated and stirred for 2 h. The mixture was centrifuged at 11,000 rpm for 5 min, and the precipitate was collected and washed three times to obtain solid silica nanoparticles.
[0043] (12) The solid silica nanoparticles were dispersed in 10 mL of deionized water, stirred continuously at 40-60 °C for 24-36 h, and the precipitate was collected and washed by centrifugation to obtain hollow mesoporous silica nanoparticles.
[0044] (2) Baicalein was prepared into a baicalein standard solution with anhydrous ethanol, and then hollow mesoporous silica nanoparticles were added into the baicalein standard solution. The mixed solution was stirred in a water bath at 50°C for 6 h, and then stirred in an open air to allow the ethanol to evaporate slowly. The mixed solution was washed with ethanol and deionized water, and then freeze-dried to obtain hollow mesoporous silica nanoparticles loaded with baicalein.
[0045] (2) Preparation of the adhesive side of Janus hydrogel carrying functional particles
[0046] (21) Add 1.5 g of N-trihydroxymethyl methacrylamide (THMA) and dissolve it in 10 mL of deionized water in a centrifuge tube, add 45 mg of polyethylene glycol diacrylate (PEGDA), and mix them thoroughly. Add 50 mg of dry and non-agglomerated mesoporous silica-coated baicalein particles, dissolve 50 mg of sodium alginate (SA) in the above solution, and add it to the silicone mold after it is fully dissolved.
[0047] (22) 25 μg of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) was added to 0.5 mL of deionized water to obtain a LAP solution. 20 μL of the LAP solution was added to 2 mL of the composite solution of step (21), mixed evenly, and irradiated with 365 nm ultraviolet light for 5 min to cure and obtain a hydrogel.
[0048] (3) Preparation of the sliding side of the Janus hydrogel: Place one side of the hydrogel on a piece of filter paper soaked in 0.4 mM borax solution for 30 seconds. Then remove the excess solution on the hydrogel with deionized water and dry it in a drying oven at 30°C for 10 minutes to obtain a Janus hydrogel that is conducive to drug release.
[0049] This embodiment prepares hollow mesoporous silica nanoparticles loaded with anti-inflammatory drug baicalin and integrates them into Janus hydrogel. The hollow mesoporous silica nanoparticles provide a lot of space for drug loading, which helps to increase the drug loading. By integrating the functional particles into the adhesion side of the Janus hydrogel, its adhesion to the tissue can be enhanced, which helps to maintain stability in a moist biological environment. The entire preparation process has clear steps, simple operation, and is easy to repeat.
[0050] Example 2
[0051] Preparation of cyclodextrin-encapsulated baicalin:
[0052] After dissolving the baicalein particles in DMSO solution to prepare a storage solution, add it to PEG300. Add Tween-80 to the solution, mix well, and continue to add physiological saline to make up the volume. Weigh the carrier material chitosan-cyclodextrin grafted polymer (CS-CD) into a beaker, add 2% glacial acetic acid, stir and dissolve at room temperature to obtain a chitosan-cyclodextrin grafted polymer solution; slowly add baicalein solution to the solution, continue stirring at room temperature for 35 hours; remove ethanol by rotary evaporation, and make up the volume with pure water; after ultrasonic treatment, centrifuge with a low-speed centrifuge and take out the supernatant.
[0053] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0054] The method for preparing cyclodextrin-encapsulated baicalin in this example optimizes the release characteristics of the drug by improving the solubility and bioavailability of the drug. Using DMSO as a solvent effectively increases the solubility of baicalin, providing convenience for further encapsulation and drug loading. The encapsulation effect of cyclodextrin not only improves the bioavailability of baicalin, but also reduces the metabolic rate and excretion rate of the drug in the body, thereby prolonging the drug's duration of action. In addition, the medium effect of PEG300 improves the release rate of the drug, making the drug release more stable and controllable. The entire preparation process has clear steps, simple operation, and is easy to repeat in the laboratory or production, ensuring the consistency and reliability of the drug preparation. Through this strategy, efficient loading and controlled release of baicalin are achieved, providing new possibilities for improving therapeutic effects and reducing side effects.
[0055] Example 3
[0056] Preparation of functional particles loaded with anti-inflammatory drugs
[0057] Quercetin was prepared into a 1 mg / mL quercetin solution with anhydrous ethanol, and then hollow mesoporous silica nanoparticles were added thereto. The mixed solution was stirred in a water bath at 60°C for 8 hours, and then stirred in an open air to allow the ethanol to evaporate slowly. After washing with ethanol and deionized water, the solution was freeze-dried to obtain hollow mesoporous silica-loaded quercetin nanoparticles.
[0058] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0059] This example demonstrates an innovative nano drug delivery system that uses carefully designed mesoporous silica nanoparticles as carriers to efficiently encapsulate quercetin, achieving targeted drug delivery and controlled release. The unique structure of hollow mesoporous silica nanoparticles not only provides a broad drug loading space, but also its high specific surface area and porous properties create ideal conditions for the uniform dispersion and slow release of drug molecules. The application of this method, especially in biomedical applications such as muscle insertion, can ensure that quercetin acts directly on the target site, thereby significantly improving the bioavailability and efficacy of the drug.
[0060] Application Examples
[0061] The purpose of constructing a rat rotator cuff injury animal model is to provide a stable experimental basis for the study of rotator cuff injury.
[0062] First, rats were anesthetized by inhalation of 1%-5% isoflurane oxygen to ensure that the rats were painless during the operation. Then, under sterile conditions, a small incision was made at the shoulder joint of the rats, the deltoid muscle was bluntly separated, the supraspinatus tendon was exposed and cut, and a full-thickness rotator cuff injury model was constructed. Subsequently, 24 SD rats were randomly divided into four groups, with 6 rats in each group, including a normal group, a rotator cuff injury group, a simple gel group, and a gel + drug group. In the simple gel group and the gel + drug group, Janus gel and drug-loaded Janus gel were implanted in the tendon injury site, respectively. After the operation, strict aseptic suture and disinfection bandage were performed to prevent infection. In the first three days after modeling, infection prevention was carried out by intramuscular injection of penicillin, and the rats were restricted from moving without immobilizing the affected limb. One week later, the rotator cuff injury model was reconstructed, including tendon braiding, tendon-bone junction treatment, hydrogel implantation, and infection prevention and wound care were continued. Three weeks after surgery, the biomechanical properties of the model were evaluated by tensile load testing to provide a scientific basis for further research on rotator cuff injury.
[0063] The results show that the Janus hydrogel of the present invention, which is conducive to drug release, is particularly suitable for preventing tissue adhesion after surgery due to soft tissue injury. For example, after surgical suture of rotator cuff injury, patients may face problems of tissue adhesion and heterotopic ossification. At this time, the material of the present invention can be used as an ideal patch to exert an anti-inflammatory effect, prevent excessive inflammation, and reduce tissue adhesion.
[0064] The results show that the Janus hydrogel of the present invention, which is conducive to drug release, is particularly suitable for preventing tissue adhesion after surgery due to soft tissue injury. In a specific application, surgical suture is first performed on a rat rotator cuff tissue injury model to simulate the clinical rotator cuff injury repair process. Subsequently, the Janus hydrogel patch of the present invention is applied to the suture site. Due to the Janus characteristics of the hydrogel, one side has the function of promoting drug release, and the other side has excellent bioadhesion, which can quickly and tightly combine with the tissue of the surgical site. The drug release surface of the Janus hydrogel can continuously release anti-inflammatory drugs, effectively control the inflammatory response of the surgical site, and prevent the occurrence of excessive inflammation. At the same time, the bioadhesive surface of the hydrogel is tightly combined with the tissue, reducing the friction between the tissues and reducing the possibility of adhesion formation.
[0065] In addition, the porous structure design of Janus hydrogel provides a suitable growth microenvironment for cells, which is conducive to cell migration and proliferation, and promotes tissue repair and functional recovery. Through this design, the hydrogel patch can not only effectively prevent tissue adhesion, but also accelerate the healing process of damaged tissue, improve the surgical effect, and reduce the patient's postoperative discomfort and complications.
[0066] like Figure 1 The results showed that both Janus hydrogel and Janus hydrogel with anti-inflammatory drugs had good biocompatibility. Although there was no significant difference between the two groups in the short term (1-3 days), the comparison of long-term effects showed that Janus hydrogel with anti-inflammatory drugs had a significant advantage.
[0067] like Figure 2 The results show the comparison of the maximum load of the rotator cuff tissue of rats in different experimental groups. The bar graph shows the maximum load of the control group, sham operation group, hydrogel group and hydrogel group with anti-inflammatory drugs added. The error bars represent the standard error of each group of data. It can be seen that the hydrogel group with anti-inflammatory drugs added showed the largest maximum load, indicating that it may be most effective in promoting rotator cuff tissue repair. The control group, as a baseline, had the highest maximum load, while the sham operation group may have suffered some damage due to the surgical operation and showed a lower maximum load. The hydrogel group was between the two, showing the positive effect of hydrogel on rotator cuff tissue repair.
[0068] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a double-sided heterogeneous drug-loaded wet hydrogel, characterized in that: The following steps are involved: (1) Preparation of functional particles loaded with anti-inflammatory drugs: (11) mixing anhydrous ethanol, water and ammonia water, stirring and dissolving in an oil bath, and then adding tetraethyl orthosilicate and continuing to stir and react; after the reaction is completed, centrifuging and washing to obtain solid silica nanoparticles; (12) dispersing the solid silica nanoparticles in water, adding anhydrous sodium carbonate, stirring for 1.5-2 hours, and then centrifuging and washing again to obtain hollow mesoporous silica nanoparticles; (13) dissolving baicalein in anhydrous ethanol, adding hollow mesoporous silica nanoparticles, stirring in a water bath, evaporating the ethanol and then freeze-drying to obtain hollow mesoporous silica-supported baicalein nanoparticles; (2) Preparation of Janus hydrogels carrying functional particles: (21) dissolving N-trihydroxymethyl methacrylamide in water, adding polyethylene glycol diacrylate, and mixing them thoroughly; adding hollow mesoporous silica-loaded baicalein nanoparticles; dissolving an appropriate amount of sodium alginate in the above solution, and after it is fully dissolved, obtaining a mixed solution, and adding the mixed solution into a silica gel mold; (22) adding phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt to water to obtain an initiator solution; The initiator solution is added to the silica gel mold containing the composite solution, mixed evenly, and then irradiated with ultraviolet light of 365-405 nm for 5-10 min to obtain a solidified hydrogel; (3) Preparation of the sliding side of the Janus hydrogel: Place one side of the solidified hydrogel in the modified solution and soak it for 30 to 45 seconds, then use water to remove excess solution on the surface of the hydrogel, wipe it with dry filter paper to form a sliding side, and obtain a double-sided heterogeneous drug-loaded wet hydrogel.
2. The method for preparing a double-sided heterogeneous drug-loaded wet hydrogel according to claim 1, characterized in that: The oil bath temperature in step (11) is 50°C; The mass ratio of anhydrous ethanol, water and aqueous ammonia is (70-75):10:(3-4); The amount of tetraethyl orthosilicate added is 3-6 ml / 100 ml of the mixed solution.
3. The method for preparing a double-sided heterogeneous drug-loaded wet hydrogel according to claim 1, characterized in that: The stirring temperature in step (12) is 40-60° C. and the stirring time is 24-36 h.
4. The method for preparing a double-sided heterogeneous drug-loaded wet hydrogel according to claim 1, characterized in that: The water bath temperature in step (13) is 50-60° C., and the water bath stirring time is 6-8 h; The mass ratio of baicalein to hollow mesoporous silica nanoparticles is 1-2:
3.
5. The method for preparing a double-sided heterogeneous drug-loaded wet hydrogel according to claim 1, characterized in that: In step (21), the mass ratio of N-trimethylol methacrylamide to polyethylene glycol diacrylate is 1:0.02-0.06; The amount of the hollow mesoporous silica-supported baicalein nanoparticles added is 1 mg / ml solution; The amount of sodium alginate added is 0.3-0.7 wt % of the total mass of the solution.
6. The method for preparing a double-sided heterogeneous drug-loaded wet hydrogel according to claim 1, characterized in that: The initiator in step (22) is LAP initiator or VA086 initiator. The concentration of the initiator solution is 100ug / ml; The added amount of the initiator is 2.5wt‰ of the mass of the mixed solution.
7. The method for preparing a double-sided heterogeneous drug-loaded wet hydrogel according to claim 1, characterized in that: The modified solution in step (3) is a borax solution or a CaCl2 solution.
8. The method for preparing a double-sided heterogeneous drug-loaded wet hydrogel according to claim 7, characterized in that: The concentration of the borax solution in step (3) is 0.4 mM, and the concentration of the CaCl2 solution is 0.9% (m / v).
9. Application of the double-sided heterogeneous drug-loaded wet hydrogel prepared according to the method according to any one of claims 1 to 8 in medical materials.